Successful treatment of calciphylaxis with intravenous sodium thiosulfate in a nonuremic patient: case report and review of therapy side effects - Fernandes, Carolina; Maynard, Bruno; Hanna, Dominique (Journal of cutaneous medicine and surgery, 2014)
AbstractBackground:Calciphylaxis is a life-threatening condition traditionally observed in patients with end-stage renal disease. Cases of nonuremic calciphylaxis have also been reported, but data on this rare condition are mainly empirical. To present a case of severe nonuremic calciphylaxis treated with intravenous sodium thiosulfate (IV STS) and to assess the implications of this treatment. Case report and review of the literature. A nonuremic patient diagnosed with distal calciphylaxis was started on IV STS after a 12-month nonresponse to conventional therapy. On week 12, the patient requested palliative care, given her many side effects (transient severe nausea and significant electrolyte imbalance). Pain subsided after 14 weeks, and complete wound healing was observed after 6 months. Based on this case report, IV STS can improve refractory calciphylaxis in nonuremic patients. However, literature on the subject remains scarce. Careful monitoring for adverse transient side effects is advised.